Surge arrester requirements study for transformer protection in 132 kV GIS substation - Abdul Malek, Zulkurnain (IEEE, 2007)
Insulation coordination study for a substation requires accurate prediction of possible overvoltages generated within or external to the substation. Protective devices in the form of surge arresters are usually installed to protect substation equipment from overvoltages caused by both switching and lightning surges. In this work, the decision whether to install or not to install ZnO surge arresters for power transformer protection in a 132 kV GIS substation was made with the aid of ATP-EMTP software. Various models such as those for underground cables and ZnO surge arresters were carefully studied since the results of the simulation study were very much dependent on the models chosen. The resulting overvoltages at the power transformer due to possible lightning impulses at various injections points were studied. A decision was finally made based on the simulation results.